Human Capital and State Civil Apparatus Development - Yosephina Ohoiwutun (East Asian Journal of Multidisciplinary Research, 2023)
This research focuses on the role of human capital in supporting the achievement of the vision and mission of public organizations. This focus is based on the assumption that organizations tend to be more rigid than private organizations, which tend to be more dynamic in dealing with change. The type of research used in this study is qualitative research. Observations are used to cross-check the data. Observations were made with the aim of exploring concrete manifestations of the results of human capital in improving ASN performance. Based on the research results, the human capital dimension is an important key to improving the performance and career development of ASNs in government organizations. Law No. 14 of 2014 concerning State Civil Apparatus Article 12 ASN states that employees who act as planners, executors, and supervisors of the implementation of general government and national development tasks through implementing policies. The human capital dimension is internal to ASN itself and does not depend on the organizational culture or existing regulations related to ASN.